The Role of Islamic Banking in Promoting Sustainable Development: A Case Study of ZISWAF Mechanism in Southeast Asia - Dewi Sundari Tanjung; Dini Vientinay; Riny Viri Insy Sinaga (CV. Barokah Publsiher, 2024)
Islamic banking in encouraging sustainable development through Islamic financial instruments, namely ZISWAF in the Southeast Asia region. This study uses a qualitative method by using literature studies as references and obtaining sources through journals, books, websites, and other supporting sources. The results of the study state that Islamic Banking plays an important role in encouraging sustainable development in Southeast Asia through the ZISWAF mechanism (Zakat, Infak, Sedekah, and Wakaf). The implementation of which must be based on sharia principles such as the prohibition of usury and emphasizing social justice makes Islamic banking in line with the achievement of the Sustainable Development Goals (SDGs). Although it has an important role, there are challenges both from society and the government, for this reason coordination is needed between the two and maintaining relations with countries in the Southeast Asia region in order to find a middle ground.​